Trajetória acadêmica na medicina: desafios, aprendizados e experiências - Parra, Muller Rodrigues (Universidade Federal de São Carlos, 2024)
This work recounts the author's academic journey in medical school, spanning from 2018 to 2024. Organized into three cycles – Basic, Clinical, and Internship – the narrative highlights challenges, learnings, and experiences throughout this trajectory. In the first cycle, covering the initial two years of the program, the author shares the initial difficulties, from adapting to active learning methodologies to choosing accommodation. The importance of integrating with peers and overcoming obstacles that shaped both academic and personal growth is emphasized. The second cycle, taking place from 2020 to 2022, is marked by changes in the curriculum and the impacts of the COVID-19 pandemic. The suspension of in-person activities is addressed, emphasizing the faculty's efforts to adapt and resume practical activities. Overcoming the challenges imposed by the pandemic situation showcases the author's resilience. The third cycle, the Internship, is described as a phase of intense transformations and responsibilities. Stages in various specialties are detailed, highlighting practical learning and relationships built with preceptors and faculty. The hospital environment contributes to consolidating theoretical knowledge gained throughout the course. The author emphasizes involvement in extracurricular activities, such as participation in the Academic Center, the Academic League of Analgesic Therapy and Palliative Care, and the Education through Work for Health Program. These complementary experiences enrich their education, providing a broader view of the healthcare system and strengthening their skills. In conclusion, the work highlights the completion of the degree as a milestone of overcoming challenges, learning, and maturation. The author celebrates not only academic achievement but also the friendships forged during this journey, underscoring the importance of mutual support among peers.
Academic journey in Medicine: challenges, learnings, and experiences
Keywords: Educação superior; Medicina; Relato de experiência; Covid-19; College; Medicine; Academic journey; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM